An Outbreak of Corynebacterium Diphtheriae Infection in Broiler Chickens in Lagos, Nigeria (Global Journal of Medical Research, 2016)
The outbreak involved 1,200 15 weeks old white leghorn growers in a poultry farm in Lagos out of which 163 died without any premonitory signs. Postmortem examination revealed congested lungs, haemorrhagic inflammation of the upper respiratory tract, crop, proventriculus and petechial haemorrhage of the cardiac muscles. Corynebacterium diphtheria was isolated from the intestine, heart blood, lung, upper respiratory tract and liver of all that died. The pathogenicity of the isolates was conducted on 8 15-weeks old white leghorn with two as controls using 0.5ml overnight broth culture administered orally. They were observed for up to 13 days with 100% mortality. The organism was re-isolated from the heart blood, liver, lung, trachea, proventiclus and crop of infected chickens. The control showed no sign of illness during the period of observation. This study revealed the zoonotic nature of Corynebacerium diphtheriae which association with poultry in Nigeria has not been reported as far as the authors knew.
Keywords: outbreak; corynebacterium diphtheriae; broiler chickens